2018
DOI: 10.2214/ajr.17.19249
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Kurtosis Imaging Combined With DWI at 3-T MRI for Detection and Assessment of Aggressiveness of Prostate Cancer

Abstract: Both ADC and K can be used as quantitative parameters in detection and assessment of aggressiveness of PCa. The combination of DKI and DWI showed no significant superiority to DWI alone in detection and assessment of the aggressiveness of PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Compared to the monoexponential signal model widely used for conventional ADC mapping, the multicompartmental RSI models examined in this study showed substantially better fits (ie, lower fitting residuals) to DWI data from the prostate. This aligns with the results of previous studies that suggest the standard monoexponential model does not adequately describe the diffusion characteristics of the prostate 15,18,32,34,35 . While PI‐RADS specifies careful application of this model only over the range of b‐values where the DWI signal can be well‐approximated by a monoexponential decay (~100–1000 sec/mm 2 ), 3 synthetic DWI methods regularly use the monoexponential model to extrapolate DWI signal far beyond this range 36,37 .…”
Section: Discussionsupporting
confidence: 83%
“…Compared to the monoexponential signal model widely used for conventional ADC mapping, the multicompartmental RSI models examined in this study showed substantially better fits (ie, lower fitting residuals) to DWI data from the prostate. This aligns with the results of previous studies that suggest the standard monoexponential model does not adequately describe the diffusion characteristics of the prostate 15,18,32,34,35 . While PI‐RADS specifies careful application of this model only over the range of b‐values where the DWI signal can be well‐approximated by a monoexponential decay (~100–1000 sec/mm 2 ), 3 synthetic DWI methods regularly use the monoexponential model to extrapolate DWI signal far beyond this range 36,37 .…”
Section: Discussionsupporting
confidence: 83%
“…The results have proved that IVIM ( 14 19 ) and DKI ( 20 24 ) may contribute to the detection and aggressiveness assessment of PCa. However, the results of IVIM and DKI for assessing the aggressiveness of PCa were various; several studies showed that IVIM ( 16 18 ) and DKI ( 22 24 ) were feasible to stratify the pathological grade of PCa, but a few studies found negative results of IVIM ( 15 ) and DKI ( 20 ) parameters in predicting the GS.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, five b values (200, 500, 1000, 1500, and 2000 mm 2 /s) were applied to acquire DKI imaging. Previous studies [11,16] have demonstrated that perfusion has prominent influence for low b values (usually < 200 mm 2 /s); nonetheless, too much high b values increase the chance of image distortion and susceptibility artifacts, especially for bowels. Therefore, considering acquisition time, we finally selected above five b values in our institution.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [20] suggested that to analyze a larger number of pixels may result in more reproducible results for the measured parameters. Furthermore, We chose consecutive three slices of ROIs (the slice with the prominent lesion section and the adjacent up and down slices), thus could decrease the deviation of sampling between cases and increase the reliability of results [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation